2006
DOI: 10.1007/s00340-006-2492-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel THz source based on a two-color Nd:LSB microchip-laser and a LT-GaAsSb photomixer

Abstract: A two-color Nd:LSB microchip-laser that simultaneously emits at 1061.3 nm and 1063.9 nm is used for photomixing. Since LT-GaAs which is typically utilized for photomixing cannot be excited efficiently with wavelengths exceeding 1 mu m, LT-GaAsSb with a bandgap energy designed to match the laser emission is used here for the first time. With this system THz radiation at 0.7 THz is generated and detected with a bolometer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The selection of the two modes can be accomplished with a suitable mode selector (e.g. an etalon) [24]. Dual color laser diodes.…”
Section: Other Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of the two modes can be accomplished with a suitable mode selector (e.g. an etalon) [24]. Dual color laser diodes.…”
Section: Other Solutionsmentioning
confidence: 99%
“…To obtain a beat frequency between two adjusted modes, some optical selectors OS (e.g. a Fabry-Perot filter) are used [24]. Figure 7 presents another example where a sophisticated optical selector is used [25].…”
Section: Introductionmentioning
confidence: 99%
“…Lasers have been widely used in military, medical, and scientific research fields due to their advantages of large energy density, high directionality, and coherence, which have greatly promoted societal development and scientific progress. All-solid-state lasers have attracted increasing attention due to their compact structure, small size, and low maintenance cost. , Usually, the all-solid-state laser can only produce a single-wavelength laser because of the limitation of active ion energy level transitions in the laser medium. With the continuous expansion of laser applications, orthogonal polarized dual-wavelength lasers generated by a single laser are required in laser medical treatment, differential absorption lidar, fine laser spectroscopy, terahertz fields, etc. Therefore, the all-solid-state orthogonal polarized dual-wavelength laser has become a hot topic of research in the fields of laser and laser crystal research.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, from these results, some questions remain, especially concerning the meaning of the measured resistivity on such thin layers taking into account surface depletion, the carrier lifetime, and the evolution of the material properties with the growth conditions. In the same way, Willer et al 21) have reported THz generation via photomixing using a 19% Sb alloy, but without any details on the material properties.…”
mentioning
confidence: 97%